LOTS to HOTS: How do mathematics teachers improve students’ higher-order thinking skills in the class? - Firdha Mahrifatul Zana; Cholis Sa'dijah; Susiswo Susiswo (International Journal of Trends in Mathematics Education Research, 2022)
This study explored how mathematics teachers improve students' thinking skills from low to higher order thinking skills (HOTS) during class. This study used a qualitative descriptive research design. The research subjects involved were mathematics teachers from one of the high schools in Malang City, East Java, Indonesia. Data were collected through a process of initial observation in schools, the results of preparing lesson plans, classroom assessments by teachers, and semi-structured interviews. The results of the research were analyzed using models, namely data reduction, data presentation, and concluding. Data focused on lesson plans based on a scientific approach and HOTS-based assessments: analyzing, evaluating, and creating. The teachers' class assessments were analyzed and classified into the HOTS cognitive level using the Anderson Krathwohls' Taxonomy indicators. The findings of this study indicate that teachers arranged the class with a scientific approach setting and provided HOTS-based class assessments to students to improve students thinking skills. But on the other hand, teachers experienced obstacles, that are students who are still passive when the scientific method was applied and the learning took a lot of time. Another obstacle related to the HOTS-based assessment is that teachers had difficulty when compiling HOTS-based assessment because it required a lot of time and thinking skill. Students also had difficulty in solving HOTS-based questions due to low reading interest and diverse student abilities.